Answer:
1. (5·sin(A) - 3·cos(A)/(4·cos(A) + 5·sin(A)) = 1/8
2. θ = 30°
3. tan(θ) - cot(θ) = (2·sin²(θ) -1)/((cos(θ)×sin(θ))
from tan(θ) - 1/tan(θ) = sin(θ)/cos(θ) - cos(θ)/sin(θ) and sin²(θ) + cos²(θ) = 1
4. tan10°·tan15°·tan75°·tan80°= 1 from;
sin(α)·sin(β) = 1/2[cos(α - β) - cos(α + β)]
cos(α)·cos(β) = 1/2[cos(α - β) + cos(α + β)]
5. x² + y² = a² + b² where x = a·cosθ - b·sinθ and y = a·sinθ + b·cosθ from;
cos²θ + sin²θ = 1
Explanation:
1. Here we have 5·tan(A) = 5·sin(A)/cos(A) = 4
∴ 5·sin(A) = 4·cos(A)
Hence to find the value of (5·sin(A) - 3·cos(A)/(4·cos(A) + 5·sin(A)) we have;
Substituting the value for 5·sin(A) = 4·cos(A) into the above equation in both the numerator and denominator we have;
(4·cos(A) - 3·cos(A)/(4·cos(A) + 4·cos(A)) = cos(A)/(8·cos(A)) = 1/8
Therefore, (5·sin(A) - 3·cos(A)/(4·cos(A) + 5·sin(A)) = 1/8
2. For the equation as follows, we have
this gives
![(2sin (\theta/2) cos (\theta/2) )/(2 cos^2 (\theta/2)) + (2 cos^2 (\theta/2))/(2sin (\theta/2) cos (\theta/2) ) = 4](https://img.qammunity.org/2021/formulas/mathematics/high-school/brqdveek0e5scfn4s7q9vkd96khedytt6n.png)
![tan(\theta)/(2) + (1)/(tan(\theta)/(2) ) = 4](https://img.qammunity.org/2021/formulas/mathematics/high-school/c8klmweq1fmscmrexdr9jttx134ykretul.png)
![tan^2(\theta)/(2) + 1 = 4* tan(\theta)/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/bep75thwql5m87up220ax8k3gknun0irpo.png)
![tan^2(\theta)/(2) - 4\cdot tan(\theta)/(2) + 1 = 0](https://img.qammunity.org/2021/formulas/mathematics/high-school/iwjvwj57xih9q7x5002560dyjck32x577c.png)
We place;
![tan(\theta)/(2) = x](https://img.qammunity.org/2021/formulas/mathematics/high-school/6neal69wzf7qfce3a1n2xodqtbg0ogvg7h.png)
∴ x² - 4·x + 1 = 0
Factorizing we have
(x - (2 - √3))·(x - (2 + √3))
Therefore, tan(θ/2) = (2 - √3) or (2 + √3)
Solving, we have;
θ/2 = tan⁻¹(2 - √3) or tan⁻¹(2 + √3)
Which gives, θ/2 = 15° or 75°
Hence, θ = 30° or 150°
Since 0° < θ < 90°, therefore, θ = 30°
3. We have tan(θ) - cot(θ) = tan(θ) - 1/tan(θ)
Hence, tan(θ) - 1/tan(θ) = sin(θ)/cos(θ) - cos(θ)/sin(θ)
∴ tan(θ) - 1/tan(θ) = (sin²(θ) - cos²(θ))/(cos(θ)×sin(θ))...........(1)
From sin²(θ) + cos²(θ) = 1, we have;
cos²(θ) = 1 - sin²(θ), substituting the value of sin²(θ) in the equation (1) above, we have;
(sin²(θ) - (1 - sin²(θ)))/(cos(θ)×sin(θ)) = (2·sin²(θ) -1)/((cos(θ)×sin(θ))
Therefore;
tan(θ) - cot(θ) = (2·sin²(θ) -1)/((cos(θ)×sin(θ))
4. tan10°·tan15°·tan75°·tan80°= 1
Here we have since;
sin(α)·sin(β) = 1/2[cos(α - β) - cos(α + β)]
cos(α)·cos(β) = 1/2[cos(α - β) + cos(α + β)]
Then;
tan 10°·tan15°·tan75°·tan80° = tan 10°·tan80°·tan15°·tan75°
tan 10°·tan80°·tan15°·tan75° =
![(sin(10^(\circ)))/(cos(10^(\circ))) * (sin(80^(\circ)))/(cos(80^(\circ))) * (sin(15^(\circ)))/(cos(15^(\circ))) * (sin(75^(\circ)))/(cos(75^(\circ)))](https://img.qammunity.org/2021/formulas/mathematics/high-school/4g5ibk6p70bgss8pu8jlwm208uayzu5b1t.png)
Which gives;
![(sin(10^(\circ)) \cdot sin(80^(\circ)))/(cos(10^(\circ))\cdot cos(80^(\circ))) * (sin(15^(\circ)) \cdot sin(75^(\circ)))/(cos(15^(\circ))\cdot cos(75^(\circ)))](https://img.qammunity.org/2021/formulas/mathematics/high-school/1hxkd26k51j5yofzwyiwx75qnu1w5mzmur.png)
![=(1/2[cos(80 - 10) - cos(80 + 10)])/(1/2[cos(80 - 10) + cos(80 + 10)]) * (1/2[cos(75 - 15) - cos(75 + 15)])/(1/2[cos(75 - 15) + cos(75 + 15)])](https://img.qammunity.org/2021/formulas/mathematics/high-school/k35jvg6ezj6zz4w00m6ggy78jnuhrid9di.png)
![=(1/2[cos(70) - cos(90)])/(1/2[cos(70) + cos(90)]) * (1/2[cos(60) - cos(90)])/(1/2[cos(60) + cos(90)])](https://img.qammunity.org/2021/formulas/mathematics/high-school/tdiohul8y9xqqes4hjth3wdufk1po82hzq.png)
![=([cos(70)])/([cos(70) ]) * ([cos(60)])/([cos(60) ]) =1](https://img.qammunity.org/2021/formulas/mathematics/high-school/lvyexz2nniwihqmx780ngzj50q60zv3y6q.png)
5. If x = a·cosθ - b·sinθ and y = a·sinθ + b·cosθ
∴ x² + y² = (a·cosθ - b·sinθ)² + (a·sinθ + b·cosθ)²
= a²·cos²θ - 2·a·cosθ·b·sinθ +b²·sin²θ + a²·sin²θ + 2·a·sinθ·b·cosθ + b²·cos²θ
= a²·cos²θ + b²·sin²θ + a²·sin²θ + b²·cos²θ
= a²·cos²θ + b²·cos²θ + b²·sin²θ + a²·sin²θ
= (a² + b²)·cos²θ + (a² + b²)·sin²θ
= (a² + b²)·(cos²θ + sin²θ) since cos²θ + sin²θ = 1, we have
= (a² + b²)×1 = a² + b²